Vegetation change analysis and ecological recovery of the copperbelt Miombo woodland of Zambia - Syampungani, Stephen (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Forest and Wood Science))--University of Stellenbosch, 2009.